Mengaplikasikan Ilmu Sosial Profetik dalam Dakwah Islam - Ardianto, Risko Aris; Fauzi, Sriyono (TSAQOFAH, 2024)
The development of the times brings controversy in human life, one of which is moral decline. Moral damage is caused by weak implementation of noble morals in life. Therefore, the role of preaching that is full of wisdom is very necessary in society. The urgency of Islamic Da'wah is the moral foundation of the nation, and religious values can become a spirit of liberation from poverty of knowledge, faith and socio-culture, as happened during the time of the Prophet Muhammad SAW. Therefore, it is worth putting forward the idea of prophetic education as a solution in Islamic da'wah. The purpose of this research is to determine the concept of prophetic education in Islamic preaching regarding the Kuntowijoyo Thought Study. This research is library research, researchers use content analysis and critical analysis methods, library research data collection techniques. The research findings of Kuntowijoyo's prophetic education concept are divided into three pillars, namely humanization, liberation and transcendence. The concept of prophetic education in da'wah: first, the humanization of da'wah focuses on caring for the surrounding environment and promoting the values of social justice. secondly, the prophetic approach of liberation in da'wah also highlights the urgency of social solidarity and concern for those who are oppressed. third, belief in the existence of Allah SWT is the basis of all existing elements of faith. From there arise various beliefs, which must be believed, understood and accepted with the mind, so that they can be trusted wholeheartedly.